Singapore : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This Selected Issues paper develops a new calibrated model of the Singapore economy, the Singapore Global Policy MODel (SGPMOD), and uses it to conduct a variety of policy experiments focused on the conduct of monetary policy. The SGPMOD is used to illustrate the role of the monetary policy responses of Singapore's monetary authority following a variety of domestic and external shocks. It is suggested that monetary policy can do little to prevent the trough in real GDP in late 2016, but it can definitely contribute to a speedier recovery. In the near term, there is general global turbulence in exchange rate markets, exacerbating the negative effects from Singapore's transmission mechanism and its reliance on the uncovered interest parity condition.